Penerapan Model Pembelajaran Video Bermain Peran dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Fiqih Materi Peradilan Islam Kelas XI IPA 3 di MAN 3 Jember - Hasanah, Siti Nur (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This research started with students who had difficulty understanding the subject matter of Fiqh, this was because the teacher still dominantly used the lecture method. So the researcher chose the Role Play method as an alternative in learning Fiqh, because in the Islamic Judiciary chapter they also have to carry out practices so that students better understand what has been taught. This research was conducted at MAN 3 Jember, in this study there was a problem, namely about how to apply the role play method in the Fiqh subject of the Islamic justice chapter and how student learning outcomes related to the chapter on Islamic justice using the role play method. This study aims to improve student learning outcomes when studying Fiqh in the Islamic justice chapter by applying a role-play learning model. The subjects of this study were students of class XI IPA 3 for the academic year 2023/2024 which consisted of 29 students. This study used a qualitative approach and was carried out using Classroom Action Research (CAR) which consisted of two cycles. The instruments used in this study were observation sheets and interviews using the method of increasing Fiqh learning outcomes. It can be seen that in the first cycle, students had a mastery level of 55.26% and in the second cycle, student mastery reached 81.57%. The results of the student learning tests in the second stage showed that there were only 3 students who did not complete and 34 people who had achieved the minimum completeness criteria of KKM from the Fiqh subject in class XI IPA 3 MAN 3 Jember. Apart from increasing learning outcomes, student activity in the learning process in class has also increased.